G197(P) Prolonged neonatal jaundice: Normal direct bilirubin levels observed in health. (24th May 2017) - Hodgson, JM; Someren, V van; Goyale, A; Smith, C
Abstract : Objective: Prolonged neonatal jaundice is common and usually benign. However assessment of bilirubin fractions is recommended to determine the need for further assessment for congenital liver disease, particularly biliary atresia. The direct (conjugated) bilirubin thresholds currently used are variable and poorly evidenced. We aimed to provide the first population-based data for healthy neonates>14 days of age in order to improve targeting of investigations. Methods: We performed a retrospective cohort analysis of split bilirubin levels, and subsequent follow-up, for all neonates initially assessed in our prolonged neonatal jaundice clinic over two years. We plotted this data against age at sampling to produce percentile charts for total, direct and direct-total bilirubin ratio levels in this population. Results: Data was collected for 420 neonates (501 blood samples) across an age range of 11–63 days. No significant liver disease was found. Total bilirubin levels decreased from a mean value at 11–17 days-old of 173.4 mmol/L (95 th percentile 253.9 mmol/L) to 143.2 mmol/L (236.7 mmol/L) at 32–42 days-old. However direct bilirubin levels altered little, with corresponding values of 14.2 mmol/L (22.9 mmol/L) and 15.2 mmol/L (26.0 mmol/L). Direct-total bilirubin ratio was very variable with some 95 th percentiles>30%. Conclusions: In a population of healthy neonates with prolonged jaundice the total bilirubin decreased with increasing age whereas the direct bilirubin remained fairly stable. The absolute direct bilirubin appears more reliable than the direct-total bilirubin ratio. Our results support NICE guidance that conjugated bilirubin >25 mmol/L constitutes an appropriate threshold for further investigation for neonatal liver disease, although more stringent criteria may also be valid.